Characterization of adherence for ti6al4v films rf magnetron sputter grown on stainless steels (2014)
Ti6Al4V films were grown on UNS S31600 austenitic stainless steel samples by RF magnetron sputtering. On top of samples, macroindentation tests were carried out to characterize the film to substrate adherence according to the recommended VDI 3198 procedure. Sputter deposition experiments varying both chamber pressure and target applied power were carried out. All films displayed superior adhesion to the substrates. A non-monotonic relationship between adherence and chamber pressure or target applied power was observed. The lowest adherences were associated with intermediate pressures and powers. The outstanding film to substrate adherence was mainly addressed to monophasic and nanometric film character (crystallite size was roughly 20 ± 10 nm) and to rather high continuity and homogeneity of films.